유두상 갑상선암에서 경부 림프절 전이에 대한 비교분석 - 이성자(Sung Ja Lee); 박범석(Beom Seok Park); 김준식(Jun Sik KimJ); 박주섭(Ju Sup Park) (Annals of surgical treatment and research, 2003)
Purpose: The management of cervical lymph node metastases from papillary thyroid cancer ranges from selective removal to a radical neck dissection. A clear understanding of the metastases of nodes at potential risk improves the quality of life (QOL) of patients, and through correct surgical methods, based on previous studies; it has been found that lymph node metastasis correlated with a high risk of recurrence. The purpose of our study was to improve the QOL of patients through an appropriate surgical method at the time of the initial operation, which decreases the risk and incidence of reoperation, by reviewing the relationship of multiple variables with cervical lymph node metastases. Methods: We retrospectively reviewed 123 consecutive patients with papillary thyroid cancer, who underwent a total thyroidectomy with modified radical neck dissection between January 2000 and December 2001. We analysed the relationship between the metastatic pattern, age, sex, tumor location and tumor size, degree of invasion, multicentricity, duration and postoperative complications, in the patients with cervical lymph node metastases. Results: Of the multiple variables, age, sex and capsular invasion were found to significantly correlate with lymph node metastases. Conclusion: In patients presenting with capsular invasion, modified radical neck dissections are recommended for palpable cervical lymph nodes, for the prevention of recurrence and reoperation, even when the statistics indicate significance in male patients, or those of a young age, although, further studies with a larger population are required. (J Korean Surg Soc 2003;64:115-120) KCI Citation Count: 3